THE EQUIVALENCE IN TRANSLATION OF PUJA TRI SANDHYA FROM INDONESIAN TO ENGLISH - Anak Agung Inten Mayuni (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
Puja Tri Sandhya is Hindus prayer known in all countries. The original prayer came in Sanskrit language, but every Hindus believer already translate the prayer into their native language. In 1950, Balinese Hindus used Puja Tri Sandhya to get the recognition from the government allowing Parisada Hindu Dharma Indonesia (PHDI)—the major reform movement and Hindus organization in Indonesia—to translate Puja Tri Sandhya into Indonesian. This translation aimed to make every Hindus believer in Indonesia knows about the meaning of the mantras. Besides Indonesian, Puja Tri Sandhya is also translated into the universal language that 20 percent of the world spoke, English. English is believed to give the best medium to other people who want to learn more about Hindus or simply just curious. As a reminder, in this paper Indonesian will be the source language (SL) and English will be the result of the translation so we shall call it target language (TL). In translation, equivalency will be the point to show if the translation is well translated or not. In their book The Theory and Practice of Translation (1959), Nida and Taber state two kinds of equivalency that the translator can use as their reference they are: formal and dynamic equivalence. Here, Puja Tri Sandhya in Indonesian and English versions will be analyzed using 2 kinds of equivalences by Nida and Taber.